How do older adult volunteer instructors describe their peer teaching experiences at a Lifelong Learning Institute (LLI) - Ilseon Choi (Adult Education Research Conference, 2006)
This paper explored peer teaching experiences of older adult volunteer instructors at a Lifelong Learning Institute (LLI). Data was collected through in-depth interviews with the instructors, observations of classes, and documents of the LLI. Analysis revealed various aspects of peer teaching of adults: participants enjoy teaching, they describe their role as facilitator of learning, interaction in class results in reciprocity, and participants voluntarily continue to develop courses and teaching materials.
Keywords: Peer teaching; LLI; older adults